Molecular and Bioinformatic Evidence of Hepatitis C Virus Evolution in Brain - Fishman, Sarah L. (2008)
BACKGROUND: Neurocognitive deficits in patients with hepatitis C virus (HCV) infection prompted a search for HCV in brain. RESULTS: HCV was present in the brains of 7 (54%) of 13 patients with viremia, as determined by 5' UTR and E1 (envelope 1) gene analysis. Brain HCV RNA consensus sequences differed from those in plasma and liver in 4 (57%) of 7 patients. The quality ofHCVRNA from postmortem brain and liver was assessed and demonstrated to be suitable for sequence analysis. Quasispecies analysis revealed that several mutations present in clones from >1 brain region were absent in clones from liver and plasma. Brain-specific mutations defined several families of related sequences. The patterns of brain-specific mutations in these families were consistent with the evolution of HCV RNA from a common ancestor. Single-nucleotide-polymorphism analysis confirmed that a prominent brain-specific mutation constituted ~10% of HCV RNA in cerebellum and medulla but that this mutation was undetectable in the liver and plasma of the same patient. CONCLUSIONS: This study introduces novel methods for assessing RNA from postmortem samples. It increases the reported cases of HCV in the brain, provides the first E1 sequences from the brain, and contributes to the growing evidence that HCV replicates and evolves within the brain.